Groundwater recharge rates and surface runoff response to land use and land cover changes in semi-arid environments - Owuor, Steven O.; Butterbach-Bahl, Klaus; Guzha, Alphonce Chenjerayi; Rufino, Mariana C.; Pelster, David E.; Díaz Pinés, Eugenio; Breuer, Lutz (Springer, 2016)
The effects of land use and land cover (LULC) on groundwater recharge and surface runoff and how these are affected by LULC changes are of interest for sustainable water resources management. However, there is limited quantitative evidence on how changes to LULC in semi-arid tropical and subtropical regions affect the subsurface components of the hydrologic cycle, particularly groundwater recharge. Effective water resource management in these regions requires conclusive evidence and understanding of the effects of LULC changes on groundwater recharge and surface runoff. We reviewed a total of 27 studies (2 modeling and 25 experimental), which reported on pre- and post land use change groundwater recharge or surface runoff magnitude, and thus allowed to quantify the response of groundwater recharge rates and runoff to LULC. Comparisons between initial and subsequent LULC indicate that forests have lower groundwater recharge rates and runoff than the other investigated land uses in semi-arid tropical/ subtropical regions. Restoration of bare land induces a decrease in groundwater recharge from 42% of precipitation to between 6 and 12% depending on the final LULC. If forests are cleared for rangelands, groundwater recharge increases by 7.8 ± 12.6%, while conversion to cropland or grassland results in increases of 3.4 ± 2.5 and 4.4 ± 3.3%, respectively. Rehabilitation of bare land to cropland results in surface runoff reductions of between 5.2 and 7.3%. The conversion of forest vegetation to managed LULC shows an increase in surface runoff from 1 to 14.1% depending on the final LULC. Surface runoff was reduced from 2.5 to 1.1% when grassland is converted to forest vegetation. While there is general consistency in the results from the selected case studies, we conclude that there are few experimental studies that have been conducted in tropical and subtropical semi-arid regions, despite that many people rely heavily on groundwater for their livelihoods. Therefore, there is an urgent need to increase the body of quantitative evidence given the pressure of growing human population and climate change on water resources in the region.